2023
DOI: 10.1177/10384162231164572
|View full text |Cite
|
Sign up to set email alerts
|

A Career Education and Development Framework and measure for senior secondary school students

Colin McCowan,
Peter McIlveen,
Brad McLennan
et al.

Abstract: Career development learning is increasingly emphasized as a curricular strategy to prepare students for their post-compulsory school transitions to further study or employment. Educators require career development frameworks and resources to support students’ reflective learning. The present research tested a hypothesized Career Education and Development Framework (CEDF) comprising eight factors: The understanding of self; opportunities; influences; goal setting; decision-making; taking action; reflecting/revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…via separate studies which administered the CEDS-Senior VN and the CEDS-Tertiary VN in samples of high school and university students. Both studies found an eight-factor model consistent with the original measure (McCowan et al, 2023) that was based on the conceptual framework of Marciniak et al (2022). The majority of CEDS subscale mean scores were relatively consistent across year levels and gender.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…via separate studies which administered the CEDS-Senior VN and the CEDS-Tertiary VN in samples of high school and university students. Both studies found an eight-factor model consistent with the original measure (McCowan et al, 2023) that was based on the conceptual framework of Marciniak et al (2022). The majority of CEDS subscale mean scores were relatively consistent across year levels and gender.…”
Section: Discussionmentioning
confidence: 59%
“…Participants respond to a 5-point Likert scale ranging from strongly disagree (1) to strongly agree (5). The original studies of two independent samples (McCowan et al, 2023) found Cronbach α coefficients of self (0.77, 0.87), influences (0.62, 0.78), opportunities (0.81, 0.87), goals (0.86, 0.90), decision-making (0.76, 0.86), taking action (0.78, 0.85), reflecting/reviewing (0.78, 0.85), and confidence (0.74, 0.86). Table 2 presents the Cronbach α coefficients found in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations